FAKTOR - FAKTOR MEMPENGARUHI MOTIVASI KADER DALAM PELAKSANAAN KESEHATAN GERAKAN 3M DI KELURAHAN TOMULABUTAO KECAMATAN DUNGINGI KOTA GORONTALO - Nelson Pomalingo (-, 2021)
Support from health cadres in assisting the implementation of health programs is lack.This could be seen in the evaluation of health program that showed the attendance level of  health cadres  at Posyandu (integrated service post) is still low. As results, the visit level of mothers was decreased at medical center. It was a phenomenon due to the role of health cadres in  Tomulabutao Village was the highest. This could be seen in the report of support level of health cadres at Posyandu (integrated service post) in Gorontalo City Health Office (Dikes, 2011). The purpose of this study was to analyze the factors related to motivation of health cadres in 3M movement in Tomulabutao Village, Gorontalo City. The type of study was survey research with cross sectional study approach, the population was the entire health cadres in Tomulabutao Village which was 60 people. The sampling technique using Exhaustic Sampling methods. The results showed there was a relationship between motivation and  3M programs  implementation in Tomulabutao Village, Dungingi District, Gorontalo City.  There was a relationship between the behavior of  cadres and 3M  programs  implementation in Tomulabutao Village, Dungingi District, Gorontalo city.Conclusions and Recommendations: to the Health Office of Gorontalo City, it is suggested to improve the participation level of health cadres in the implementation of health programs by improving the incentives to health cadres in order to strenghten their motivation to assist the health workers.